Problems which Confront Renal Transplant Recipients - Jaddoue, Batool; AL-Mallah, Suhban (Iraqi National Journal of Nursing Specialties, 2008)
Objective: The study objectives are to identify the problems which confront renal transplant recipients ( RTRS). Methodology: A descriptive study was carried out at two Teaching Hospitals with kidney transplant centers. Surgical specialties and Al-Karama outpatients, clinics for ( RTRS) ,and three Teaching Hospitals; Medical city, Al-Karama and Al-Yermok which were responsible for immunosuppressive drugs distribution .Starting from October ,1st 2006 to the end of July 2007.To achieve the objectives of study, a non-probability (purposive) sample of 150 ( RTRS) who were attending to the outpatient clinic of the above listed hospital were selected according to the criteria of the study sample . The finalized questionnaire contained (83) items. The content validity of the instrument was established through penal of (14) experts. Reliability of the problems scales was determined by test-retest method which was estimated as average (r=0.76). Data was gathered by interview technique using the questionnaire format and data was analyzed by application of descriptive and inferential statistical methods. Results: The results of the study indicated that the ( RTRS) confront (83 ) problems and affected by these problems with different severity level, high, moderate, and low. Recommendation: According to the results of this study, the researcher recommended that the provision of the necessary post transplant medicines from easy to reach centers.